Biomarkers to personalize treatment with 177Lu-PSMA-617 in men with metastatic castration-resistant prostate cancer - a state of the art review. (March 2022) - Heidegger, Isabel; Kesch, Claudia; Kretschmer, Alexander; Tsaur, Igor; Ceci, Francesco; Valerio, Massimo; Tilki, Derya; Marra, Giancarlo; Preisser, Felix; Fankhauser, Christian D.; Zattoni, Fabio; Chiu, Peter; et al.
Radioligand therapy with Lutetium-177 (177Lu)-Prostate-specific membrane antigen (PSMA) has shown to prolong survival in metastatic castration resistant prostate cancer (mCRPC). One of the major challenges for clinicians in the future is to select those patients who would benefit most from this therapy to position it in the treatment landscape of mCRPC. This, in turn, will lead to the delivery of personalized therapies. In this narrative review article we summarize recent studies investigating both predictive and prognostic clinical, imaging-based, and molecular biomarkers to predict treatment response to 177Lu-PSMA-617 radioligand therapy with the aim of identifying men who should be considered for this approach. Of note, the evidence on the role of biomarkers currently relies on small retrospective trials and their validation in larger prospective cohorts is necessary before these results can be translated in the clinical practice.